2018
DOI: 10.1111/ajt.14650
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes expressing the self-antigens myosin and vimentin play an important role in syngeneic cardiac transplant rejection induced by antibodies to cardiac myosin

Abstract: Long-term success of heart transplantation is hindered by humoral and cell-mediated immune responses. We studied preexisting antibodies to two cardiac self-antigens, myosin and vimentin, and exosomes induced by antibodies to self-antigens in eliciting immune responses to cardiac grafts. After syngeneic heterotopic murine heart transplantation, rabbit anti-myosin or normal rabbit immunoglobulin was administered at days 0 or 7. Sera were collected after heartbeat cessation and cellular infiltration was analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 37 publications
0
43
0
1
Order By: Relevance
“…Tregs suppress humoral responses either indirectly by reducing CD4 + T cell help, or directly by cell‐to‐cell interactions with B cells . Because a significant proportion of recipient‐derived APCs can acquire intact donor MHC molecules through the uptake of donor exosomes and/or trogocytosis, this may be a mechanism by which dsCAR‐Tregs could directly suppress recipient‐derived B cells. Moreover, our data suggest that the dsCAR‐Tregs themselves can also acquire donor MHC molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs suppress humoral responses either indirectly by reducing CD4 + T cell help, or directly by cell‐to‐cell interactions with B cells . Because a significant proportion of recipient‐derived APCs can acquire intact donor MHC molecules through the uptake of donor exosomes and/or trogocytosis, this may be a mechanism by which dsCAR‐Tregs could directly suppress recipient‐derived B cells. Moreover, our data suggest that the dsCAR‐Tregs themselves can also acquire donor MHC molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A proteome analysis of extracellular vesicles also identified vimentin in EVs released from microglia (Drago et al, 2017). Noteworthy, a very recent finding demonstrated serum exosomes to contain vimentin in a murine cardiac explant model system (Sharma, Liu, Perincheri, Gunasekaran, & Mohanakumar, 2018).…”
Section: Exosomal Release Of Vimentinmentioning
confidence: 91%
“…Exosomes were isolated from serum samples of LTxRs with RVI and from stable controls by ultracentrifugation as previously described. 21,24,25 Exosome purity was validated using the sucrose cushion method. 21,26 The presence of the exosome-specific markers CD9 (312102, BioLegend, San Diego, CA) and Alix (634502, BioLegend) was assessed using immunoblot.…”
Section: Exosome Isolation and Validationmentioning
confidence: 99%
“…Immunization of C57BL/6 mice with exosomes from LTxRs diagnosed with RVI and stable controls Exosomes (10 mg/100 ml) isolated from LTxRs with RVI or from stable controls were used for immunization of C57BL/6 mice ( Days 1,7,18,and 25). Prior experiments have demonstrated that injury to the native lungs is required for Abs to lung SAgs to cause lesions.…”
Section: Determination Of Lung Sags 20s Proteasome and Viral Antigementioning
confidence: 99%